Synthesis of micro-mesoporous materials ZSM-5/FDU-12 and the performance of dibenzothiophene hydrodesulfurization - Zhang, H.; Han, L.; Duan, A.; Xu, C.; Zhao, Z.; Wei, Y.; Jiang, G.; Liu, Jian; Wang, D.; Xia, Z. (Royal Society of Chemistry, 2017)
The micro-mesoporous materials ZF-x (ZSM-5-FDU-12, x = SiO 2 /Al 2 O 3 ) with different molar ratios of SiO 2 /Al 2 O 3 were synthesized by an in situ nano-assembly method with the ZSM-5 precursor serving as the silica source. The physicochemical properties of the supports and the corresponding catalysts were analyzed in detail by various techniques including SEM, TEM, XRD, nitrogen physisorption, FTIR, UV-Vis, pyridine IR, Raman and XPS. The nitrogen physisorption measurement showed that the composite ZF-130 possessed excellent physical properties compared to other ZF-x materials. In addition, the XPS spectra displayed that catalysts NiMo/ZF-x showed a higher sulfurization than NiMo/FDU-12, and the NiMo/ZF-130 exhibited the highest contents of MoS 2 and NiMoS. In addition, DBT was employed as the probe molecule to evaluate the HDS (hydrodesulfurization) performance of the sulfide catalysts of NiMo/ZF-x under different weight hourly space velocities (WHSVs) 20-120 h -1 , while NiMo/FDU-12 was used as the reference. Furthermore, the relationship between the structure of micro-mesoporous materials and the HDS activities of catalysts was systematically evaluated. The HDS efficiencies followed the order NiMo/ZF-130 > NiMo/ZF-110 > NiMo/ZF-150 > NiMo/ZF-90 > NiMo/ZF-70 > NiMo/FDU-12 under the operation conditions of 340 °C, 4.0 MPa, and H 2 /oil of 200 20-120 h -1 . Compared to other NiMo/ZF-x catalysts, NiMo/ZF-130 displayed the highest efficiency of DBT HDS, 96.3% at 20 h -1 , which could be attributed to the synergistic effects of its larger pore sizes (14.9 nm), greater specific surface area (352 m 2 g -1 ), moderate B and L acid sites, and the highest ratios of Mo 4+ /Mo (58%) and NiMoS/NiT (64%).